A Virtual International Faculty Development Design to Provide Remote Flipped Teaching Training During the COVID‐19 Pandemic - Gopalan, Chaya (FASEB J, 2021)
The COVID‐19 pandemic forced universities to adopt emergency remote teaching strategies. This sudden switch from face‐to‐face teaching to online format prompted appropriate faculty training by the institutions. A university in Saudi Arabia organized a faculty development program to train its educators to design and implement a virtual classroom using the flipped teaching (FT) method. The flipped classroom is a student‐centered instructional design where students are expected to learn basic concepts on their own using resources provided by the instructor outside of class. The class time is used to rehearse and master this knowledge through discussion and application. Moving lectures outside of class allows opportunity to engage students with the content using student‐centered activities during class where more interaction between the faculty and students as well as among peers is expected. The present study tested the effectiveness of a remote faculty training program at an international institution in the development of their own remote flipped courses. The training was stretched over six biweekly sessions for which a course was created on Moodle, the Learning Management System. The participants (n=13) were guided to develop pre‐class assignments such as lecture videos, formative assessments to encourage students in pre‐class preparation, in‐class student engagement activities, and assessments. The faculty participants were given a pre‐ and a post‐training survey to learn about their knowledge, attitude, and confidence towards FT. The pre‐course survey results indicated that 62% of the participants had never tried FT and about 46% were not familiar with FT prior to receiving training while only 54% felt ready to flip. However, all participants intended to implement the FT method after completing the course. Following the training, all participants reportedly felt they could confidently flip their courses and implement FT strategies. All participants valued the training and hoped to reconvene monthly as a group to continue meeting as a group to share their remote FT experiences. In conclusion, the virtual FT training helped improve the knowledge, skills, attitudes, and confidence of all participants in designing their flipped courses to engage students in the remote teaching mode.